2009
DOI: 10.1016/j.ccr.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Leukemia-Initiating Cells in a Conditional Knockin Model of an Imatinib-Responsive Myeloproliferative Disorder

Abstract: SUMMARY Despite remarkable responses to the tyrosine kinase inhibitor imatinib, CML patients are rarely cured by this therapy perhaps due to imatinib-refractoriness of leukemia-initiating cells (LICs). Evidence for this is limited because of poor engraftment of human CMLLICs in NOD-SCID mice and non-physiologic expression of oncogenes in retroviral transduction mouse models. To address these challenges, we generated mice bearing conditional knockin alleles of two human oncogenes: HIP1/PDGFβR (H/P) and AML1-ETO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…6 Inhibition of ABL-kinase alone is not sufficient to completely eliminate LSC/Ps, presumably due to drug refractoriness. 7 However, mechanistic studies on downstream signals responsible for the BCR/ABL-mediated transformation phenotype are hindered by the lack of studies in HSC-initiated in vivo models. 8 Rac GTPases play integral roles in HSC and progenitor (HSC/P) proliferation, survival, homing, and engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…6 Inhibition of ABL-kinase alone is not sufficient to completely eliminate LSC/Ps, presumably due to drug refractoriness. 7 However, mechanistic studies on downstream signals responsible for the BCR/ABL-mediated transformation phenotype are hindered by the lack of studies in HSC-initiated in vivo models. 8 Rac GTPases play integral roles in HSC and progenitor (HSC/P) proliferation, survival, homing, and engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to providing a driving force for tumor growth and maintenance, CSC may display different sensitivity to cytotoxic drugs and radiotherapy than the bulk tumor cell population that they generate (8)(9)(10). Thus, in at least some tumor types, CSC may withstand conventional anticancer therapy consistent with their presumed role in relapse following therapy, while possibly responding to approaches that impair pluripotency.…”
Section: Introductionmentioning
confidence: 99%
“…Because CSCs are characterized from various types of cancers, CD44 has been a useful marker for enriching CSCs not only for breast tumors but also a variety of other epithelial tumor models (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). We and others have previously reported that CSCs are more resistant to traditional cancer therapies (4,18,19). There is circumstantial evidence that CSCs may be involved in metastasis of solid tumors, including breast cancer.…”
mentioning
confidence: 99%